Effects of Light Quality on the Circadian Rhythm of Leaf Movement of a Short-Day-Plant - Halaban, Ruth (1969)
Studies were made of the effects of blue, green, red and far-red (FR) light on the circadian rhythm of leaf movement of Coleus blumei × C. frederici, a short day plant. Under continuous illumination with blue light, there was a significant lengthening of the period of the rhythm to about 24.0 hr, as compared to 22.5 hr in continuous darkness. Under continuous red light, the period length was significantly shortened to 20.5 hr. Under continuous green or FR, the period length was not significantly different from the dark control. It was observed that under continuous FR illumination, the leaves tended to oscillate in a more downward position. Eight-hr red light signals were effective in advancing the phase of the rhythm as compared to a control under continuous green light. Blue light signals were effective in delaying the phase of the rhythm. FR light signals were ineffective in producing either delay or advance phase shifts. Far-red light did not reverse the effects of either red or blue light signals. On the basis of these results it is suggested, that pigments which absorb blue or red light, rather than phytochrome, mediate the effect of light on the circadian rhythm of leaf movement.